Assessment of nurses' knowledge of the prevention of hospital-associated venous thromboembolism in a tertiary health institution in Nigeria - Patricia Obiajulu Onianwa; Folashade Omobisi Mary Akanbi; Mary Oyenike Ayorinde; Oluwatosin Esther John; Olufunke Olabisi Are; Ogonna Eze Ojerinde; Sariyat Yetunde Alaka (Wolters Kluwer Medknow Publications, 2023)
Objective: This study assessed the level of nurses' knowledge of the prevention of venous thromboembolism (VTE) in a tertiary health institution. Materials and Methods: This descriptive cross-sectional study was conducted with 328 eligible respondents, selected using a random sampling method in a teaching hospital in Nigeria. A self-administered structured questionnaire was used to collect data on the basic knowledge, risk factors, and preventive measures of VTE. Results: Findings from the study revealed that 51.2% scored above the mean score of 28.6 ± 3.1. The educational status of the respondents had a significant influence on their knowledge of risk factors of VTE (F = 4.696, P = 0.031). Conclusion: The overall knowledge of nurses is satisfactory, although the majority could not answer correctly questions on the administration of prefilled anticoagulants and identification of some key risk factors of VTE.